2011
DOI: 10.1109/tbcas.2011.2176937
|View full text |Cite
|
Sign up to set email alerts
|

SoC CMOS UWB Pulse Radar Sensor for Contactless Respiratory Rate Monitoring

Abstract: An ultra wideband (UWB) system-on-chip radar sensor for respiratory rate monitoring has been realized in 90 nm CMOS technology and characterized experimentally. The radar testchip has been applied to the contactless detection of the respiration activity of adult and baby. The field operational tests demonstrate that the UWB radar sensor detects the respiratory rate of person under test (adult and baby) associated with sub-centimeter chest movements, allowing the continuous-time non-invasive monitoring of hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
83
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(84 citation statements)
references
References 12 publications
0
83
0
1
Order By: Relevance
“…The compliance of the transmitted pulse sequence with the FCC mask is also reported in [3]. The results of the field operational tests reported in [3] validated the effectiveness of the novel UWB planar differential antenna presented herein for the implementation of low-cost UWB pulse radars for short-range applications.…”
Section: B Stand-alone Antennamentioning
confidence: 66%
See 2 more Smart Citations
“…The compliance of the transmitted pulse sequence with the FCC mask is also reported in [3]. The results of the field operational tests reported in [3] validated the effectiveness of the novel UWB planar differential antenna presented herein for the implementation of low-cost UWB pulse radars for short-range applications.…”
Section: B Stand-alone Antennamentioning
confidence: 66%
“…Field operational tests carried out in [3] demonstrated that the UWB radar sensor detects correctly sub-centimeter movements of targets (13×13, 13×26 and 26×26 cm) made of plasterboard covered by aluminum foil, as well as the movements of the chest due to the respiratory activity (including apneas) of the person under test, be they adults (both genders) or infants [3]. All the additional details about the field operational tests of the complete radar sensor can be found in [3]. The compliance of the transmitted pulse sequence with the FCC mask is also reported in [3].…”
Section: B Stand-alone Antennamentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] One of the most critical circuits of modern radiofrequency transceivers is the local oscillator, i.e., an autonomous circuit operating as the \pulsing heart" of such systems, in an analogy with the human body. As any other Despite these results provide a¯rst interesting perspective, this is limited by the comparison between a di®erential topology, i.e., cross-coupled common-source differential pair, and two single-ended topologies, Colpitts and Hartley.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Li et al reported a hybrid radar system combining the advantages of single-tone and FMCW radars [17]. With very high-range resolution owing to its wideband nature, IR-UWB radars have been efficiently implemented on silicon [18] and have the potential for realizing accurate detection of respiratory rate and apnea in adults and infants [19]. Above all, each type of radar system can implement the noncontact vital sign detection, depending on the specific application.…”
Section: Introductionmentioning
confidence: 99%